2018
DOI: 10.1002/jper.17-0726
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates of hybrid rough surface implants and their alveolar bone level alterations

Abstract: Hybrid rough surface implants had high survival rate, stable bone level, and low prevalence of biological complications. This surface design demonstrated promising clinical outcomes. More studies are needed to further support the clinical advantages of hybrid surface implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Univariable analyses using the log rank test for categorical variables, and Cox regression for continuous variables, were performed for each covariate to identify its association with survival or success. 23 Hazard ratios (HR) with survival or success were further calculated for covariates with significance (P < 0.05) in the log rank test or Cox regression analysis. Covariates having the P value ≤0.25 were selected for multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Univariable analyses using the log rank test for categorical variables, and Cox regression for continuous variables, were performed for each covariate to identify its association with survival or success. 23 Hazard ratios (HR) with survival or success were further calculated for covariates with significance (P < 0.05) in the log rank test or Cox regression analysis. Covariates having the P value ≤0.25 were selected for multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the porous structure in the present study has possible problems, such as a higher risk of bacterial plaque accumulation, mucosal and peri-implant diseases when compared to the machined surface upon exposure to complex oral environments [34]. Hybrid surface implants have been suggested to reduce the prevalence of peri-implantitis by including the machined surface or less roughened texture in the coronal part of the implant together with the rough surface treatments in the apical part, which played important role in healing between the bone and the surface [35]. In correspondence with the rationale of the hybrid implant, the test group implant was expected to have both advantages in terms of accelerated healing and increased bone-to-implant contact by the porous structure at the apical part, and less biological complications related to the inflammation at the coronal smooth surface area.…”
Section: Discussionmentioning
confidence: 99%
“…The machined coronal part reduces the presence of biofilm by reducing wettability and cell adhesion at this level, and the treated or roughened part favors osseointegration [ 19 ]. Hybrid implants have a high survival rate, marginal bone stability, and fewer biological complications [ 20 ]. However, animal studies have shown that implants with a hybrid surface present a degree of inflammation of the peri-implant tissues similar to that of implants with moderate roughness [ 21 ] and a greater marginal bone loss [ 22 ].…”
Section: Introductionmentioning
confidence: 99%